FORMS OF AFFLICTION AND IDENTITY IN GRAHAM SWIFT‟S NOVELS - Mărginean, Alexandra Roxana (European Scientific Journal, ESJ, 2014)
This paper looks at forms of affliction in Graham Swift‘s novels. The idea is to analyse these in order to see the way identity is constructed by the characters in some special circumstances that test one‘s physical endurance, nerves and resolve. The first case scenario we are looking at is the objectification of one‘s body, going beyond the classical instance of women being reduced to sex objects, and looking at the way one‘s gaze may objectify a man as well, in a totally different sense than a sexual one. For this latter example we go into Lacan‘s theory about the mirror image. Other special instances of objectification under analysis are the symbolical reduction of the person to a dummy or an automaton, the implications of which are dwelled on in detail. The second part of the paper gets into more concretely violent forms of abuse – mutilated bodies, either in war or by torture, rape and even murder/suicide – explaining their impact on the characters‘ psychological profile and the personality/identity modifications that they entail. The conclusion of the paper is that apparently destructive elements may display building potential when it comes to identity.